2012
DOI: 10.7861/clinmedicine.12-5-410
|View full text |Cite
|
Sign up to set email alerts
|

FAST enough? The UK general public’s understanding of stroke

Abstract: -Good public awareness of stroke symptoms and the need for rapid admission to hospital can improve patient outcomes. However, evidence suggests that this awareness is currently inadequate. Therefore, it is important to identify gaps in public knowledge to target public health campaigns appropriately. This questionnaire study of 356 adults in Birmingham city centre assessed the general public's understanding of stroke, whether demographic factors affect this and the influence of a national campaign (FAST) on kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(46 reference statements)
1
11
1
Order By: Relevance
“…In our study, diabetes mellitus was less frequent risk factor for CVS as 16.8% of participants reported it when close-ended question was asked. This result was negative when compared to previous studies about diabetes mellitus as risk factor for CVS in UK [17] 62.4%, in Hong Kong [16] 60%, in Spain [8] 59%, in Georgia [15] 69%, in India [18] 31%, in Pakistan [11] 33.4%, and in Oman [12] 22.8%, while this result was positive when compared to the result of Benin [10] 0.3%.…”
Section: Risk Factors Of Csvcontrasting
confidence: 72%
See 1 more Smart Citation
“…In our study, diabetes mellitus was less frequent risk factor for CVS as 16.8% of participants reported it when close-ended question was asked. This result was negative when compared to previous studies about diabetes mellitus as risk factor for CVS in UK [17] 62.4%, in Hong Kong [16] 60%, in Spain [8] 59%, in Georgia [15] 69%, in India [18] 31%, in Pakistan [11] 33.4%, and in Oman [12] 22.8%, while this result was positive when compared to the result of Benin [10] 0.3%.…”
Section: Risk Factors Of Csvcontrasting
confidence: 72%
“…This result was in agreement with different studies that showed the most frequent identifiable risk factor for stroke was as follows. In Ain Shams and Fayoum University study [13], 73.8% was hypertension and 54.9% was stress; in Spain [8], 92% was hypertension; in South Korea [14], 68% was stress; in Georgia [15], 96% was hypertension; in Hong Kong [16], 90% was hypertension; in UK [17], 94.1% was hypertension; in Benin [10], 34.5% was hypertension and 7.6% was stress; in India [18], 54% was hypertension; in Pakistan [11], 69.1% was hypertension and 55.8% was stress; and in Oman [12], 34.5% was hypertension.…”
Section: Risk Factors Of Csvmentioning
confidence: 99%
“…The FAST to call emergency medical services message, developed in the UK, has been adopted as the main stroke public education message by stroke advocacy organizations in several countries, including the USA, Australia, and the UK. Sixty‐two per cent of parents were familiar with the FAST to call emergency medical services acronym for the symptoms of stroke, at similar rates to a recent UK study, suggesting that public education programmes are reasonably effective, even in younger adults …”
Section: Discussionsupporting
confidence: 58%
“…Sixty-two per cent of parents were familiar with the FAST to call emergency medical services acronym for the symptoms of stroke, at similar rates to a recent UK study, suggesting that public education programmes are reasonably effective, even in younger adults. 24 The study has several limitations. The different methods of patient selection for the AIS and migraine groups, and the retrospective data entry for patients with AIS presenting after hours, are sources of study bias.…”
Section: Discussionmentioning
confidence: 98%
“…Further, many people did not know what the acronym stood for. [20] Among the nearly 1·4 billion people in China, only about 0·8% (i.e., up to 10 million people excluding Hong Kong) of the population is considered capable of speaking English. [21] Thus, it is very clear that direct usage of "FAST" will be ineffective.…”
mentioning
confidence: 99%